An Analytical Study of Deposit Collection and Fund Mobilization in Developng Countries : A Financial Apprroach to Nepalese Commercial Banks in Nonlinear Analysis - Karna, Santosh Kumar; Sahani, Suresh Kumar (PALAPA, 2024)
In this research paper, we have studied the ways applying for making deposit in Nepalese commercial banks and fund mobilization behaviour shown by them to generate income for paying interest on deposit to customers. Documentation and institutionalization of deposit for the purpose of making investment into productive sectors are considered as good practices of income generation and economic development of people.